Neoliberalism as Shape-Shifter: The Case of Aboriginal Title and the Northern Gateway Pipeline. Issue 8 (2nd August 2016) - Rossiter, David A.; Wood, Patricia Burke
ABSTRACT: Neoliberalism is a political economic ideology whose proponents adopt diverse project strategies to achieve similar goals. The Northern Gateway Pipeline proposal to carry bitumen from the oil sands in Alberta to the coast of British Columbia (BC) is one such project. Developing the concept of the "shape-shifter" employed by Aboriginal legal scholars, we highlight neoliberalism's disruptive effects as it negotiates the province's history of Aboriginal land claims. Proposed in 2010, the Northern Gateway project has been controversial, seemingly pitting environmentalists against developers. At the same time, recent court decisions have placed resource development inextricably in the context of Aboriginal title; governments are obliged to consult and accommodate affected First Nations. Responses to these requirements reveal neoliberal strategies that consistently aim to fix the landscape for the investment of capital but collide with an equally determined claim of Aboriginal sovereignty. Neoliberalism is a "shape-shifter" obscuring the unresolved question of Aboriginal title.